GARY BECKER'S CONTRIBUTION TO THE ECONOMICS OF MATCHING AND MARRIAGE. (24th March 2015) - Chiappori, Pierre-André
Abstract : In his seminal, 1973 paper, published in the Journal of Political Economy, Gary Becker emphasizes marriage as a crucial, yet understudied issue to which economic analysis could, therefore should, be applied. In his words:"Yet, one type of behavior has been almost completely ignored by economists, although scarce resources are used and it has been followed in some form by practically all adults in every recorded society. I refer to marriage." (p. 814)